Increased Diagnostic Accuracy of Digital vs. Conventional Clock Drawing Test for Discrimination of Patients in the Early Course of Alzheimer’s Disease from Cognitively Healthy Individuals - Müller, Stephan; Preische, Oliver; Heymann, Petra; Elbing, Ulrich; Laske, Christoph (Frontiers in Aging Neuroscience, 2017)
The conventional Clock Drawing Test (cCDT) is a rapid and inexpensive screening tool for detection of moderate and severe dementia. However, its usage is limited due to poor diagnostic accuracy especially in patients with mild cognitive impairment (MCI). The diagnostic value of a newly developed digital Clock Drawing Test (dCDT) was evaluated and compared with the cCDT in 20 patients with early dementia due to AD (eDAT), 30 patients with amnestic MCI (aMCI), and 20 cognitively healthy controls (HC). Parameters assessed by dCDT were time while transitioning the stylus from one stroke to the next above the surface (i.e. time-in-air), time the stylus produced a visible stroke (i.e. time-on-surface), and total-time during clock drawing. Receiver-operating characteristic (ROC) curves were calculated and logistic regression analyzes have been conducted for statistical analysis. Using dCDT, time-in-air was significantly increased in eDAT (70965.8 ms) compared to aMCI (54073.7 ms; p = .027) and HC (32315.6 ms; p < .001). In addition, time-in-air was significantly longer in patients with aMCI compared to HC (p = .003), even in the aMCI group with normal cCDT score (54141.8 ms; p < .001). Time-in-air using dCDT allowed discrimination of patients with aMCI from HCs with a sensitivity of 81.3% and a specificity of 72.2% while cCDT scoring revealed a sensitivity of 62.5% and a specificity of 83.3%. Most interestingly, time-in-air allowed even discrimination of aMCI patients with normal cCDT scores (80 % from all aMCI patients) from HCs with a clinically relevant sensitivity of 80.8% and a specificity of 77.8%. A combination of dCDT variables and cCDT scores did not improve the discrimination of patients with aMCI from healthy controls. In conclusion, assessment of time-in-air using dCDT yielded a higher diagnostic accuracy for discrimination of aMCI patients from HCs than the use of cCDT even in those aMCI patients with normal cCDT scores. Modern digitizing devices offer the opportunity to measure subtle changes of visuo-constructive demands and executive functions that may be used as a fast and easy to perform screening instrument for the early detection of cognitive impairment in primary care.